PENYELENGGARAAN TATA PEMERINTAHAN YANG BAIK DI LINGKUNGAN PEMERINTAH KECAMATAN DI KOTA SAMARINDA - . Djumadi; Pracahaya Pradana Putra; Yayuk Rifqi Masruroh; . Syamsinar; Rido Cahyawan; Abdul Kadir Jailani (Jurnal Paradigma (JP), 2019)
The principles of good governance are characteristics that must be met in the implementation of good governance, which relates to the control of a government in order to achieve the results desired by stakeholders. Hence the research on the implementation of good governance, which is reviewed through the application of a number of principles of good governance in the regional government in the regional government becomes a means to assess the fulfillment of public needs by the government. This study compares the implementation of good governance in several sub-district governments in the city of Samarinda, which shows that the application of the principles of accountability, transparency and justice/equality still needs improvement so that it can be carried out better for meeting community expectations. Keywords: good governance, accountability, transparency, responsiveness.